Detoxifying Escherichia coli for endotoxin-free production of recombinant proteins. Issue 1 (December 2015) - Mamat, Uwe; Wilke, Kathleen; Bramhill, David; Schromm, Andra; Lindner, Buko; Kohl, Thomas; Corchero, José; Villaverde, Antonio; Schaffer, Lana; Head, Steven; Souvignier, Chad; Meredith, Timothy; et al.
Abstract Background Lipopolysaccharide (LPS), also referred to as endotoxin, is the major constituent of the outer leaflet of the outer membrane of virtually all Gram-negative bacteria. The lipid A moiety, which anchors the LPS molecule to the outer membrane, acts as a potent agonist for Toll-like receptor 4/myeloid differentiation factor 2-mediated pro-inflammatory activity in mammals and, thus, represents the endotoxic principle of LPS. Recombinant proteins, commonly manufactured inEscherichia coli, are generally contaminated with endotoxin. Removal of bacterial endotoxin from recombinant therapeutic proteins is a challenging and expensive process that has been necessary to ensure the safety of the final product. Results As an alternative strategy for common endotoxin removal methods, we have developed a series ofE. coli strains that are able to grow and express recombinant proteins with the endotoxin precursor lipid IVA as the only LPS-related molecule in their outer membranes. Lipid IVA does not trigger an endotoxic response in humans typical of bacterial LPS chemotypes. Hence the engineered cells themselves, and the purified proteins expressed within these cells display extremely low endotoxin levels. Conclusions This paper describes the preparation and characterization of endotoxin-freeE. coli strains, and demonstrates the direct production of recombinant proteins with negligible endotoxin contamination.